2019
DOI: 10.1186/s12889-019-7252-9
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of acute dengue infection in paediatric clinics in Cameroon

Abstract: Background Dengue fever is the world’s fastest spreading mosquito borne viral infection. It is prevalent throughout both subtropical and tropical region, and affects over 128 countries. Dengue virus (DENV) infection poses a serious global public health challenge to three billion people, resulting in approximately 200 million cases of morbidity and 50,000 cases of mortality annually. In Cameroon like in most sub-Saharan African countries, DENV infection occur concurrently with other infectious dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 46 publications
7
54
2
Order By: Relevance
“…More specifically, ZIKV has recently been detected in Cameroon in Yaoundé and in the Fako Division [40]. Furthermore, a recent study found acute dengue in children living in urban and semi-urban areas of Dschang [46]. The potential vectors of these arboviruses in Cameroon include Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, ZIKV has recently been detected in Cameroon in Yaoundé and in the Fako Division [40]. Furthermore, a recent study found acute dengue in children living in urban and semi-urban areas of Dschang [46]. The potential vectors of these arboviruses in Cameroon include Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Entomological surveys can then provide important insights into the influence of urban planning and prevention on arboviral epidemics. In the western part of Cameroon, very few studies have examined the circulation of arboviruses in human populations and the presence of mosquito vectors [42,46,47]. Given the lack of studies looking at the mosquito composition after urbanisation in western Cameroon, we undertook an entomological survey to identify potential sylvatic, urban and bridge-vector species that could potentially play a role in current or future virus spillover from wild to more urbanised areas.…”
Section: Introductionmentioning
confidence: 99%
“…Aedes -borne diseases such as dengue especially were once considered scarce in Cameroon. However, during the past decade, cases of dengue have increasingly been reported [ 35 , 36 , 37 , 38 , 39 ] suggesting an active circulation of this virus in Cameroon. In addition, vector competence analysis showed that both Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent study found 11.7% and 10.4% of DENV circulating in Dschang and Bagangté respectively [10], all situated in the western highland. Another study revealed acute dengue in children living in urban and semi-urban areas of Dschang [32]. A mosquitobased arbovirus surveillance system might therefore help as a supplement to assess the presence of such arboviruses in the locality and in the whole country.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent review, Braack and colleagues [1] Orthobunyavirus genus, Bunyaviridae family. These findings originate from many studies that have investigated the prevalence of arboviruses in Cameroon mainly based on the serodiagnostic of blood samples collected from humans [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Chikungunya Virus and Zika Virus)mentioning
confidence: 99%